177k views
3 votes
which equation results from isolating a radical term and squaring both sides of the equation for the equation

which equation results from isolating a radical term and squaring both sides of the-example-1

2 Answers

1 vote

Answer:

D.
c-2=25+c+10√(c)

Step-by-step explanation:

We have been given a radical equation
√(c-2)-√(c)=5. We are asked to find the equation that results from isolating a radical term and squaring both sides of the equation for the equation.

Add
√(c) on both sides:


√(c-2)-√(c)+√(c)=5+√(c)


√(c-2)=5+√(c)

Square both sides:


(√(c-2))^2=(5+√(c))^2

Using radical rule
\sqrt[n]{a^n} =a, we will get:


c-2=(5+√(c))^2

Using perfect square formula
(a+b)^2=a^2+2ab+b^2, we will get:


c-2=5^2+2*5√(c)+(√(c))^2


c-2=25+10√(c)+c


c-2=25+c+10√(c)

Therefore, option D is the correct choice.

User Get
by
6.0k points
4 votes

Answer:

D) c - 2 = 25 + c + 10√c

Explanation:

The given equation is
√(c - 2) - √(c)  = 5


√(c -2) = 5 + √(c) \\

Taking square on both sides, we get

Here we used ( a+ b)^2 = a^2 + b^2 + 2ab formula.

c - 2 = 5^2 + (√c)^2 + 2(5)√c

c - 2 = 25 + c +10√c

Answer: D) c - 2 = 25 + c + 10√c

Thank you.

User Bidoubiwa
by
5.7k points